2019
DOI: 10.1161/hypertensionaha.119.12927
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Effects on Dahl Salt-Sensitive Hypertension, Renal Damage, and the T Lymphocyte Transcriptome

Abstract: The Dahl salt-sensitive (SS) rat is an established model of SS hypertension and renal damage. In addition to salt, other dietary components were shown to be important determinants of hypertension in SS rats. With previous work eliminating the involvement of genetic differences, grain-fed SS rats from Charles River Laboratories (SS/CRL; 5L2F/5L79) were less susceptible to salt-induced hypertension and renal damage compared with purified diet-fed SS rats bred at the Medical College of Wisconsin (SS/MCW; 0.4% NaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…In the Dahl SS rats blood pressure increase occurs in two phases: early reversible phase, which lasts 3-7 days, followed by the second phase that lasts weeks and is associated with irreversible kidney damage. 32,33 Figure 1A shows a schematic protocol of our experiment, where SS and SS Nox4−/− male rats fed a normal salt diet (0.4% NaCl) were switched to an HS (4% NaCl) chow for either 3 days or 3 weeks with subsequent 24-hours urine collections and analysis. Figure 1 illustrates that the HS diet increases urinary volume and sodium excretion similarly to earlier reports.…”
Section: Nox4 Deletion Increases Hs-induced Diuresis and Natriuresimentioning
confidence: 99%
“…In the Dahl SS rats blood pressure increase occurs in two phases: early reversible phase, which lasts 3-7 days, followed by the second phase that lasts weeks and is associated with irreversible kidney damage. 32,33 Figure 1A shows a schematic protocol of our experiment, where SS and SS Nox4−/− male rats fed a normal salt diet (0.4% NaCl) were switched to an HS (4% NaCl) chow for either 3 days or 3 weeks with subsequent 24-hours urine collections and analysis. Figure 1 illustrates that the HS diet increases urinary volume and sodium excretion similarly to earlier reports.…”
Section: Nox4 Deletion Increases Hs-induced Diuresis and Natriuresimentioning
confidence: 99%
“…9 Dahl SS rats from Charles River Laboratories (SS/ CRL), whose colony originated from SS/MCW breeders in 2001, are instead maintained on a 0.75% NaCl grain-based diet (5L79, LabDiet) and found to be remarkably protected from salt-induced hypertension and renal damage compared to SS/MCW rats fed the purified diet. 10,11 Over a decade's worth of research has demonstrated that the differences in the severity of salt-sensitive hypertension between the colonies is mediated by dietary components other than salt. [12][13][14][15] More specifically, this effect of the purified vs grain diet has been attributed to the difference in dietary protein source (casein vs wheat gluten), 12 where there is a clear contribution of the adaptive immune system.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] More specifically, this effect of the purified vs grain diet has been attributed to the difference in dietary protein source (casein vs wheat gluten), 12 where there is a clear contribution of the adaptive immune system. [13][14][15] Our recent efforts to understand the influence of the non-sodium components of the diet on salt-sensitive hypertension and renal damage have demonstrated that these changes are related to substantial differences in DNA methylation 16 and gene expression 11 in T-lymphocytes which alter the inflammatory phenotype and ultimately disease severity. As a result of the significant immune-mediated dietary effects observed in the Dahl SS rat and the increasing evidence for the role of the gut microbiota in hypertension and immunity, we hypothesized that the gut microbiota compositions of SS/MCW and SS/CRL are driven by these dietary alterations.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we have shown that a HSD induces T lymphocyte infiltration to the kidney, a process which has been described in DSS rats mainly by Mattson's group [31][32][33]. The pivotal role of this infiltration process in the DSS model has been demonstrated by a recent study which observed that T-cell-deficient DSS rats are protected from HTN induced by a HSD and a splenocyte transfer exacerbates salt-sensitive HTN [34].…”
Section: Discussionmentioning
confidence: 58%